Sympecma paedisca Brauer in Mecklenburg nebst Bemerkungen zu ihrer Verbreitungsgeschichte. - Kühlmann, Dietrich (Contributions to Entomology = Beiträge zur Entomologie, 1957)
1. In 1953 and 1954 Sympecma paedisca Brauer was found at two places of East Mecklenburg. So this species is now recorded from five areals in Central Europe. - 2. On account of its present disjunctive distribution in the western part it may be supposed, that its original province of distribution continually extended from Japan through the temperate palaearctic region as far as Netherlands and Switzerland. Later on the original territory of this species in the western part was perhaps broken to the present exclaves in the course of extension of the woods in Central Europe. - 3. "Stenökie" in Sympecma paedisca Brauer could not be ascertained. This species seems to prefer stagnant waters with abundant littoral plants. - 4. Sympecma paedisca Brauer and the related Sympecma fusca v. d. L. have not yet been found together at the same place. Further observations are needed, however, to ascertain that these species exclude each other.